Epistemología y didáctica de las ciencias. Un análisis de segundo orden - López Rupérez, F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This work shows an analysis of the relations ship between epistemology and science learning research. In this context, the progressive character of research programmes in Lakatos's philosophy of science is invoked in order to clarify the place of the non -refuted results of the Piagetian School in the evolution of the Constructivist Paradigm. Several conclusions for the progress of Science Education are also presented.